Uso da tenecteplase no transoperatório de coelhos hígidos tratados com facoemulsificação - Piveta, Lidiana Cândida (2016)
Cataracts is the treatable eye diseases that cause most blindness in the world. The effective treatment is surgical and phacoemulsification the most applied technique. Some complications are associated with the procedure as corneal opacities, uveitis and fibrin deposits. The presence of fibrin in the anterior chamber is associated with the formation of synechia and secondary glaucoma low visual recovery of patients. Some medications, as TPA (Tissue Plasminogen Activator) which acts in the degradation of fibrin, seeing being used to soften these deposits. Tenecteplase is a third generation of the synthetic TPA and have a longer half-life than the others with application in ophthalmology without damage to the cornea and retina of rabbits and humans. The study was conducted on 15 rabbits of New Zealand race, share in three groups GC, GT and GNT. The GNT and GT were surgery by phacoemulsification technics, GT was treated with 0.1 ml intracameral tenecteplase (50 μg) transoperative. The rabbits were evaluated in M0 moments - when selected, underwent phacoemulsification surgery and reassessed in M1d – 1th day M3d – 3th day M7d – 7th day M15d - 15th day and M21d – 21th days. In the clinical evaluation of the use of intracameral tenecteplase in transoperative and postoperative complications were observed, emphasizing the change in IOP, the corneal edema, fibrin deposits, hyphema, aqueous flare and synechia incidences. In the M21d animals were sacrificed, and samples of aqueous humor were collected for physical-chemical analysis (pH, density, concentration of chloride ions and total proteins). No statistical differences were observed in the clinical evaluation of the GC and GNT within the recommended parameters. In physical-chemical analysis of aqueous humor showed no statistical difference between the three groups in terms of pH and concentration of chloride ion. The density values and total protein concentration between the GC and the other groups.